1984
DOI: 10.1104/pp.74.2.413
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation to High CO2 in Bean

Abstract: ABSTRACIYoung bean plants (Phaseolus vulgaris L. cv Seafarer) grew faster in air enriched with CO2 (1200 microliters per liter) than in ambient CO2 (330 microliters per liter). However, by 7 days when increases in overall growth (dry weight, leaf area) were visible, there was a significant decline (about 25%) in the leaf mineral content (N, P, K, Ca, Mg) and a drop in the activity of two enzymes of carbon fixation, carbonic anhydrase and ribulose 1,5-bisphosphate (RuBP) carboxylase under high CO2. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(34 citation statements)
references
References 13 publications
3
31
0
Order By: Relevance
“…2). This GUS expression pattern for bCA2 coincides with the leaf CA activity levels reported in pea (Pisum sativum; and bean (Phaseolus vulgaris; Porter and Grodzinski, 1984) and also fits with the observed EST abundance in TAIR microarray data (Schmid et al, 2005;Winter et al, 2007;Ferreira et al, 2008) as well as RNAseq data (Table I). Our results are in contrast to those of Wang et al (2014), who observed little or no GUS staining in the leaf with their bCA2 promoter.…”
Section: Discussionsupporting
confidence: 52%
“…2). This GUS expression pattern for bCA2 coincides with the leaf CA activity levels reported in pea (Pisum sativum; and bean (Phaseolus vulgaris; Porter and Grodzinski, 1984) and also fits with the observed EST abundance in TAIR microarray data (Schmid et al, 2005;Winter et al, 2007;Ferreira et al, 2008) as well as RNAseq data (Table I). Our results are in contrast to those of Wang et al (2014), who observed little or no GUS staining in the leaf with their bCA2 promoter.…”
Section: Discussionsupporting
confidence: 52%
“…Efforts to understand the physiological nature of the photosynthetic decline in plants exposed to long-term elevated CO2 have focused on chloroplast damage due to excessive carbohydrate accumulation (6, 29), on feedback inhibition associated with low utilization of photosynthate (6,8,22,23), and on changes in Rubisco activity (20,22,30). Starch often accumulates in chloroplasts in response to longterm elevated CO2 (3,6,29).…”
Section: Introductionmentioning
confidence: 99%
“…Other reports have suggested that plant CA activity is regulated by light intensity and COz concentration, parameters known to influence levels of Rubisco activity (Reed and Graham, 1981). For example, in both cucumber and bean, levels of CA and Rubisco were reduced when plants were grown at elevated levels of COz (Porter and Grodzinski, 1984;Peet et al, 1986). Most recently it was noted that a decrease in Rubisco abundance obtained by rbcS antisense expression also resulted in a major decline in CA abundance, whereas other Calvin cycle enzymes were unaffected by the reduced Rubisco levels (Hudson et al, 1992).…”
mentioning
confidence: 99%